The impact of farrowing room noise on sows’ reactivity to piglets - Chapel, Nichole M (Transl Anim Sci, 2018)
Despite much interest in sow welfare, the impact of the acoustic environment on sow reactivity to her piglets is rarely considered. The objective of this study was to understand the impact of noise produced by mechanical ventilation and other sows on a sow’s reactivity to her piglets. Sows were farrowed in one of three environments: 1) with eight other sows exposed to constant fan noise (GROUP-FAN; n = 10), 2) alone with fan noise present (ISO-FAN; n = 10), and 3) alone without fans running (ISO-QUIET; n = 10). Sows were subjected for 5 min to a piglet removal event (REMOVAL) by an unknown handler twice, at 24 and 48 h postfarrowing. During a REMOVAL, sows were observed via video recording for changes in posture, eating and drinking behavior, and head orientation. Audio was recorded to quantify vocalizations by the sow. Once piglets were returned, sows underwent further behavior observations for 10 min (RETURN), resulting in approximately 15 min of total video observation. Sows were classified as young (second and third parity) and old (fifth parity and older). The YOUNG sows tended to be more Alert (looking toward the handler or their piglets) during REMOVE than OLD sows (P = 0.07; 2.01 and 1.33, respectively). The ISO-FAN sows vocalized the loudest during REMOVAL (P < 0.001) with ISO-QUIET sows performing the quietest vocalizations (GROUP-FAN: 72.22 ± 1.06 dB; ISO-FAN: 73.61 ± 1.07 dB; ISO-QUIET: 67.41 ± 0.99 dB). During RETURN, YOUNG sows spent more time sitting than OLD sows (P < 0.01; 7.48 ± 1.6% and 0.91 ± 1.8%, respectively). The ISO-QUIET sows tended to have more posture changes during the RETURN with ISO-FAN having the least changes (P = 0.06; GROUP-FAN: 1.23 ± 0.4; ISO-FAN: 0.44 ± 0.3; ISO-QUIET: 1.61 ± 0.4). Finally, sows decreased the amount of time Alert in the second RETURN (P = 0.03; first: 3.9 ± 0.6%; second: 2.5 ± 0.6%). Overall, sows acclimated to the removal and return events with decreased vocalizations and decreased Alert behaviors in the second REMOVAL and RETURN. Additionally, YOUNG sows performed more active behaviors than OLD sows, indicating that sows may become less interested in or cannot hear their piglets as they age. Finally, there is some indication that ventilation presence has an effect on sow–piglet communication with ISO-FAN sows having the loudest vocalizations when compared with sows without ventilation noise, indicating that ventilation noise may be a possible competitor with a sow’s ability to communicate with her piglets.